Graphitic carbon nitride "reloaded": Emerging applications beyond (photo)catalysis - Liu, Jian; Wang, H.; Antonietti, M. (RSC Publishing, 2016)
© The Royal Society of Chemistry 2016. Despite being one of the oldest materials described in the chemical literature, graphitic carbon nitride (g-C3N4) has just recently experienced a renaissance as a highly active photocatalyst, and the metal-free polymer was shown to be able to generate hydrogen under visible light. The semiconductor nature of g-C3N4has triggered tremendous endeavors on its structural manipulation for enhanced photo(electro)chemical performance, aiming at an affordable clean energy future. While pursuing the stem of g-C3N4related catalysis (photocatalysis, electrocatalysis and photoelectrocatalysis), a number of emerging intrinsic properties of g-C3N4are certainly interesting, but less well covered, and we believe that these novel applications outside of conventional catalysis can be favorably exploited as well. Thanks to the general efforts devoted to the exploration and enrichment of g-C3N4based chemistry, the boundaries of this area have been possibly pushed far beyond what people could imagine in the beginning. This review strives to cover the achievements of g-C3N4related materials in these unconventional application fields for depicting the broader future of these metal-free and fully stable semiconductors. This review starts with the general protocols to engineer g-C3N4micro/nanostructures for practical use, and then discusses the newly disclosed applications in sensing, bioimaging, novel solar energy exploitation including photocatalytic coenzyme regeneration, templating, and carbon nitride based devices. Finally, we attempt an outlook on possible further developments in g-C3N4based research.